Clinical study of experimentally induced vitamin E and selenium deficiency in Awassi ewes and their newborn lambs: H.K. Abood, A. M. H. Judi and A.A. AL-Ani - Abood, H. K. (The Iraqi Journal of Veterinary Medicine, 2012)
Experimental induction of vitamin E and selenium deficiency by deficient diet was carried out on Awassi ewes and their newborn lambs. The clinical signs were characterized by sudden death in 4 lambs out of 14 lambs in deficient group and other lambs showed a variable signs included inability to suckle, arched back, weakness, dullness, emaciation and recumbency. Serum selenium and vitamin E levels of these lambs were 0.01 ppm and 0.34 mg/L respectively. The clinical signs in ewes included loss of body weight and loss of wool, Weakness, dullness and recumbency. Serum selenium and vitamin E levels of these ewes were 0.02 ppm and 0.61mg/L respectively. It was concluded that vitamin E and selenium are essential antioxidants and their deficiency exposes the sheep industry to many serious losses.